Performance Annotation: Analysis of Maria Callas' Interpretive Vocal Ornamentation in George Bizet's Aria Habanera - Clarissa Jessy Setiawan; Ni Wayan Ardini; I Made Kartawan; Gede Pasek Putra Adnyana Yasa (Journal of Aesthetics, Creativity and Art Management, 2026)
The aria Habanera from Georges Bizet's opera Carmen showcases Carmen's sensual and free characterization through its distinctive melody and rhythm. Although this work has been widely researched, specific studies of vocal ornamentation are rare. Ornamentation plays a crucial role in enriching interpretation while balancing artistic freedom with fidelity to the score.  This study asks: how can Maria Callas's interpretive ornamentation serve as a reference for performing the Habanera? The methods used include transcriptions of vocal ornamentation by Maria Callas Elina Garanca and Teresa Berganza, followed by interpretive analysis to understand artistic expression and intent. A comparative analysis is conducted to assess its suitability to the score and its expressive impact on characterization. The result is a singer's note framework that can be utilized by singers and vocal educators, as well as a contribution to the musicological study of interpretive ornamentation in French opera.